The Influence of Brand Image, Product Quality and Service Quality on Customer Loyalty of Kidz Station Trans Studio Mall Cibubur East Jakarta - Muhammad Haekal Azhari; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze the influence of Brand Image, Product Quality and Service Quality. The results of the study using primary data in the form of a questionnaire to 94 customers of Kidz Station TSM Cibubur East Jakarta who have made the purchase process 2 times or more, show the result that there is a negative effect of Brand Image on Customer Loyalty and on Service Quality and Product Quality shows results that have a positive effect on Customer Loyalty. There is a positive influence on Product Quality and Service Quality indicating that Product Quality and Service Quality can be important factors for Customer Loyalty and must be continuously developed in order to continue to compete with similar competitors.